CIVIL LIABILITY IN MEDICINE IN THE LEGAL SYSTEM OF THE REPUBLIC OF NORTH MACEDONIA - Ampovska, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The Macedonian legal system doesn’t contain special rules on the liability of medical institutions and medical staff for damage that is caused while providing health services. This implies that the general rules of civil liability, which can be found in Macedonian Law on Obligations, apply to professional liability of physicians and medical institutions. The comparative law shows that the rules of contractual and non-contractual liability, fault and strict liability as well as vicarious liability can be applied in the cases of the liability mentioned above. The aim of this paper is to present the existing rules on liability in the Macedonian legal system that will apply in cases of civil liability in medicine, as well as to present an analyze of cases of liability that differ from one another and their specifics. Differing the cases of liability has its legal consequence of deciding on which liability rules are applicable, the rules on contractual or non-contractual liability. The legal relationship between a patient and physician is firstly a contractual relationship and in these cases the treatment contract is the base of patients’ and physicians’ rights, requests and obligations. Also, the application of the rules of fault liability is predominant in comparative law, but in the present the mass usage of medical devises and the introduction of high technology into medicine in general have resulted in the tendency to increase the application of strict liability in practice. Which of these tendencies and cases are accepted in the Macedonian legal system and under what conditions are they applied in legislation and in practice is a question that this paper aims to answer.